PENGEMBANGAN BAHAN AJAR BERBASIS FLIPBOOK PADA MATA PELAJARAN IPAS KONSEP “MAGNET,LISTRIK DAN TEKNOLOGI UNTUK KEHIDUPAN” KELAS V SD NEGERI KEDUNGDALEM 3 PROBOLINGGO - Yulia Agustin; Ribut Prastiwi Sriwijayanti; Ani Anjarwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted to identify problems in learning at SD Negeri Kedungdalem 3 Probolinggo, especially class V. The results of the study showed that the low interest in reading students and less interactive learning methods make students quickly bored, difficult to concentrate in understanding the material and easily lose focus or motivation to learn. Therefore, innovation of teaching materials is needed that are more interesting, interactive, and easy to understand so that learning becomes more effective so that it can increase student learning motivation. This study aims to develop flipbook-based teaching materials on the concept of Magnets, electricity and technology for life and analyze their validity and effectiveness in science learning. The method used is Research and Development (R&D) using the ADDIE model, which includes analysis, design, development, implementation, and evaluation. Data collected through questionnaires from validators, namely material experts, media experts, class teachers, and student responses. After going through the validation and revision process based on input from experts and users, the product has been declared feasible to be implemented. The results of the study showed that flipbook-based teaching materials were proven effective with a score of 86% from material experts, 93% from media experts, 90% from users/homeroom teachers, and 90% from student responses, indicating that the product was very feasible to use in the learning process. This study can be further developed with a wider scope of material and variations of other learning media to further increase student motivation and involvement in learning.